DEVELOPING AN INTEGRATED INTER-ISLAND MARITIME TRANSPORTATION MODEL FOR LOCAL ECONOMIC ADVANCEMENT: EVIDENCE FROM HUAMUAL BELAKANG DISTRICT, MALUKU PROVINCE - Suratmi Nurlette; Izaac Tonny Matitaputty; Muhammad Bugis (RADJA PUBLIKA, 2026)
This study aims to analyze existing conditions, identify key constraints, and formulate an optimal and sustainable inter-island maritime transportation development model in Huamual Belakang District, West Seram Regency, Maluku Province. This study utilized a qualitative case study approach and the data was collected through field observations, in-depth interviews, and document analysis. The analysis is supported by SWOT analysis and Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices to assess internal and external conditions. The findings indicate that the current maritime transportation system is not yet optimal, as reflected in disparities in port infrastructure capacity, an imbalanced vessel-to-population ratio (1:1,916), high operational costs, and fragmented institutional arrangements. Despite these limitations, the region demonstrates substantial local economic potential and promising opportunities for digital technology convergence. Based on the analysis, the proposed development model emphasizes an integrated approach that combines a hub-and-spoke system with Hatu Port as the primary hub, integration of supply chains for leading commodities, particularly fisheries and cloves, supported by cold storage facilities, cross-subsidy mechanisms through a Public Service Obligation (PSO) scheme, and the adoption of a digital platform, “E-Sampan,” to improve efficiency and accessibility. Strategic recommendations focus on institutional consolidation through the establishment of an integrated management authority, capacity enhancement of feeder port infrastructure, the addition of seaworthy vessels, and strengthening human resources through training and certification programs. The implementation of this model is expected to serve as a catalyst for improved connectivity, reduced logistics costs, and accelerated inclusive and sustainable local economic growth.